FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Lily; Ferry Suhardjo (E-Jurnal Akuntansi TSM, 2022)
The objective of this study is to empirically examine the factors that influence tax aggressiveness. This study uses independent variables earnings management through discretionary accrual, ROA, DAR, firm size, capital intensity, inventory intensity, firm risk and tax aggressiveness as the dependent variable. The study was conducted on 67 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 with 201 research data that accordance the criteria set using the purposive sampling method. Hypothesis testing in this study using multiple linear regression analysis. The result of this research is that ROA have an influence on tax aggressiveness. While the earnings management, DAR, firm size, capital intensity, inventory intensity, and firm risk have no influence on tax aggressiveness.